Design of single cylinder variable compression ratio 4-stroke engine - Firdaus Haikal, Ramli (2012)
This thesis is about designing a new method to increase engines efficiency. The method used in this study is variable compression ratio (VCR) engines, where the compression ratio of the engine can be changed according to driving conditions. A mechanism of VCR is designed and simulated. The motion analysis is used to analyze the VCR mechanism and engines component behaviour under different compression ratio. Solidworks simulation software is used to perform the motion analysis. The data of stress distribution, deformation of engines component and factor of safety (FOS) from the simulation are used to determine whether the components are safe to operate at compression ratio higher than the original. Yamaha FZ150i engine has been chosen as the baseline engine design. The engine are disassembled and modelled in solidworks in order to perform the simulation. The engine is simulated at 2000 rpm and the compression ratio are varies between 8:1 and 18:1. The result from of the simulation indicates that the compression ratio can safely be increased up to 12:1 with the original engines component specifications. If higher compression ratio wanted to be used, the specification of the engines component (piston and connecting rod) needed to be changed .However, since the Factor of safety (FOS) value of the components is critical at certain compression ratio, the fatigue and thermal analysis is purposed to be carried out in order to obtain more accurate result.